The Influence of Career Development, Organizational Culture, Motivation and Work Compensation on Employee Loyalty - Nabila, Shafwa Cinta; Mansur, Amin (Human Capital and Organizations, 2025)
This study aims to determine how employee loyalty is influenced by career development, organizational culture, motivation, and pay, while reviewing these relationships from an Islamic perspective. The study focused on 76 employees from the BNI Head Office (Pejompongan Building). Its uniqueness lies in combining Islamic principles emphasizing ethics, justice, and maslahah (public welfare) with traditional management approaches. While previous research has examined these factors, few have explored them through an Islamic lens. Data was collected via a questionnaire and analyzed using multiple linear regression. The findings revealed that (1) career development, (2) organizational culture, (3) motivation, and (4) compensation each have a positive and significant partial impact on employee loyalty. These results highlight that career growth opportunities, strong organizational values, meaningful motivation, and fair compensation are crucial for fostering loyalty. Managers who incorporate these four factors into their human resource strategies are more likely to build a loyal, motivated, and productive workforce. Consistent and comprehensive implementation of these aspects not only enhances employee satisfaction but also supports the company’s long-term goals in alignment with ethical and socially responsible principles rooted in Islam.